Integrating Technology in English Language Teaching (ELT) - Challenges and Barriers - Ramya, D.; Poongodi, O. T. (International Journal of Psychosocial Rehabilitation, 2020)
This paper is examining the development of English language teaching (ELT) with the integration of information and communication technology (ICT). It also studies about teachers’ perceptions on how this integration can improve the teaching and learning processes and also enhancing the teaching practices for the first year engineering English classrooms. The researcher tries to explore on some of the obstacles that obstructs the success integration of using technology in their teaching process. Questionnaire is used to collect the data from 25 English language teachers working in an engineering college at a select district. The analysis of the data discovered that ICT tools integration plays significant role in teaching process and also states some of the barriers which hinders the teachers to integrate ICT in their teaching.